2019
DOI: 10.1117/1.jmi.6.1.013501
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of multiple mixed contrast and tissue compositions using photon-counting spectral computed tomography

Abstract: Quantitative material decomposition of multiple mixed, or spatially coincident, contrast agent (gadolinium and iodine) and tissue (calcium and water) compositions is demonstrated using photon-counting spectral computed tomography (CT). Material decomposition is performed using constrained maximum likelihood estimation (MLE) in the image domain. MLE is calibrated by multiple linear regression of all pure material compositions, which exhibits a strong correlation (R 2 > 0.91) between the measured x-ray attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…The other reason could be around the similarities in the elemental composition that is The spatial accuracy obtained in our study was consistent to that of previously reported studies using similar image acquisition and MD methods [12], [16]. Another study conducted by Curtis and Roeder [7], using different image acquisition parameters and MD methods, reported quantitative accuracy of Gd as RMSE ≈ 2 mM or 0.3 mg/mL. The measured RMSE of Gd in our study was found between 0.38 to 0.8 mg/mL (2 to 5 mM, respectively) across four different tube currents.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The other reason could be around the similarities in the elemental composition that is The spatial accuracy obtained in our study was consistent to that of previously reported studies using similar image acquisition and MD methods [12], [16]. Another study conducted by Curtis and Roeder [7], using different image acquisition parameters and MD methods, reported quantitative accuracy of Gd as RMSE ≈ 2 mM or 0.3 mg/mL. The measured RMSE of Gd in our study was found between 0.38 to 0.8 mg/mL (2 to 5 mM, respectively) across four different tube currents.…”
Section: Discussionsupporting
confidence: 92%
“…The gadolinium solutions were prepared by serially diluting Multihance (Gadobenate dimeglumine, Bracco Diagnostics Inc., Princeton, NJ, USA) in water. Gadolinium was used as it is considered to be an economically viable element for photon-counting CT contrast agents due its high atomic number (64) and K-edge (52 keV) [1], [7]. Previous in vitro and animal studies with conventional CT has also demonstrated that gadolinium provides higher CT signal generation [34], [35].…”
Section: B Imaging Samples-phantoms and Biological Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…We have in previous publications shown that decomposition into more than two basis materials is feasible in phantom studies with this detector [20,21]. This has also been demonstrated with other PCDs with phantoms [26][27][28][29][30][31], anatomical specimens [27,28,32], and animal models [33,34]. The purpose of this work is to provide proof of concept that unbiased three-material decomposition with iodine can be achieved in a clinical specimen with human tissue with an experimental photon-counting silicon detector in a bench-top setup.…”
Section: Introductionmentioning
confidence: 73%
“…S PECTRAL computed tomography (CT) has recently emerged following the advancement in the photoncounting X-ray detection technology [1], [2], [3], [4], [5]. The photon-counting detectors are able to resolve the energy of the received photons and, thereby, distribute the photons into discrete channels according to their energies.…”
Section: Introductionmentioning
confidence: 99%